The comparison of sperm motility and density in four different goldfish (Carassius auratus) types - Nagy, Borbála; Bernáth, Gergely; Várkonyi, Levente; Molnár, József; Láng, Levente Zete; Izsák, Tibor; Bartucz, Tamás; Iittzés, István; Ittzés, Áron; Urbányi, Béla; Bokor, Zoltán (Acta Agraria Debreceniensis, 2022)
Different goldfish types play an important role both in ornamental fish farming and science. Considering its historical background, the goldfish is a suitable model animal for the study of artificial selection as well as for developmental biological studies. Sperm motility and cell density is an important parameter in determining sperm quality. The aim of our study was to examine the effects of different goldfish types on the sperm quality. Several sperm motility parameters (progressive motility (pMOT, %), straight line velocity (VSL, μm s-1), curvilinear velocity (VCL, μm s-1), linearity (LIN, %), amplitude lateral Head Displacement (ALH, μm), Beat Cross Frequency (BCF, Hz)) of four different goldfish types (Common goldfish-“wild type” N=5, Shubunkin N=4, Black Moor N=4, Oranda N=5) was compared during 60 hours (at 12-hour intervals) at refrigerated storage (4 °C). The variability of sperm density was also investigated in all types. A similar cell concentration was determined in the four goldfish variants (Common goldfish 2.01*1010 ± 3.46*109; Shubunkin 1.71*1010 ± 3.25*109; Black Moor 1.66*1010 ± 3.02*109; Oranda 1.56*1010 ± 5.83*109). Statistically significant difference between the 4 goldfish types in the motility parameters and cell density was not noted. However, a decreasing tendency in Black Moor sperm motility parameters (pMOT, VCL and VSL) was observable, as well as a reduced spermatozoa density in Oranda was also recorded. Our results can contribute to the improvement of the common hatchery propagation of goldfish. Future studies can add more evidence of the possible effects of artificial selection on the reproduction in different goldfish types.